Outside, inside - Pham, LeUyen (Roaring Brook Press, 2021)
"Something strange happened on an unremarkable day just before the season changed. beautiful book that describes the impact of COVID-19 on communities and why some essential workers could not quarantine. Everybody who was outside . . . went inside. Outside, it was quieter, wilder, and different. Inside, we laughed, we cried, and we grew. We remembered to protect the ones we love and love the ones who protect us. While the world changed outside, we became stronger on the inside and believed that someday soon spring would come again."--Provided by publisher.